2000
DOI: 10.1128/aac.44.4.1085-1088.2000
|View full text |Cite
|
Sign up to set email alerts
|

Antipneumococcal Activities of GAR-936 (a New Glycylcycline) Compared to Those of Nine Other Agents against Penicillin-Susceptible and -Resistant Pneumococci

Abstract: GAR-936, a new glycylcycline, had lower MICs (<0.016 to 0.125 g/ml) for 201 penicillin-and tetracyclinesusceptible and -resistant pneumococcal strains than tetracycline (<0.06 to 128 g/ml), minocycline (<0.06 to 16.0 g/ml), or doxycycline (<0.06 to 32.0 g/ml). GAR-936 was also bactericidal against 11 of 12 strains tested at the MIC after 24 h, with significant kill rates at earlier time points.The incidence of pneumococcal resistance to penicillin G and other ß-lactam and non-ß-lactam compounds has increased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 16 publications
(14 reference statements)
1
32
0
Order By: Relevance
“…The efficacy of tigecycline has also been proved in a rat model of experimental endocarditis involving both methicillin-resistant S. aureus and vancomycinsusceptible and -resistant Enterococcus faecalis isolates (13). Although tigecycline, like other derivatives of tetracycline, demonstrated bacteriostatic activity, Hoellman et al (9) showed that it was bactericidal for S. pneumoniae after 24 h, with significant killing rates at earlier time periods. The pharmacokinetics of tigecycline in healthy volunteers were linear.…”
mentioning
confidence: 99%
“…The efficacy of tigecycline has also been proved in a rat model of experimental endocarditis involving both methicillin-resistant S. aureus and vancomycinsusceptible and -resistant Enterococcus faecalis isolates (13). Although tigecycline, like other derivatives of tetracycline, demonstrated bacteriostatic activity, Hoellman et al (9) showed that it was bactericidal for S. pneumoniae after 24 h, with significant killing rates at earlier time periods. The pharmacokinetics of tigecycline in healthy volunteers were linear.…”
mentioning
confidence: 99%
“…In addition, it has been shown to be active against microorganisms known to be resistant to other classes of antimicrobial agents (1,11,12,19,20,22). Recent studies have found that the age of the broth medium used for in vitro susceptibility testing can affect the MICs of tigecycline by as much as two to eightfold (5, 21).…”
mentioning
confidence: 99%
“…Tigecycline is the first member of the glycylcycline class to be developed for clinical use. It displays potent in vitro activity against gram-positive and certain gram-negative pathogens, with MICs at which 90% of strains are inhibited (MIC 90 s) being Յ0.5 g/ml for S. aureus (including methicillin-resistant S. aureus) and S. pneumoniae (including penicillin-resistant S. pneumoniae) (7,9,15,16). Furthermore, it displays activity against those pathogens resistant to tetracyclines (7,19).…”
mentioning
confidence: 99%